Creation of low density starting plasma with small frame antenna at Uragan-3M device - Kozulya, M.M.; Kramskoy, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Lozin, A.V.; Kasilov, A.A.; Grigor’eva, L.I.; Kulaga, A.E.; Maznichenko, S.M.; Mironov, Yu.K.; Romanov, V.S.; Chechkin, V.V. (Вопросы атомной науки и техники, 2015)
Deficient shot-to-shot stability of Uragan-3M discharges makes difficult to reproduce experimental results over the period of experimental session. An efficient way of reducing difference between shots is creation of initial low density plasma before the main discharge to start up. A RF pre-ionization in the same frequency range as that of the main discharge is used in the Uragan-3M torsatron. The pre-ionization provides stable discharges during the whole experimental campaign. The main parameters of the pre-ionization plasma are measured and discussed. Нестабильность разрядов Урагана-3М затрудняет воспроизведение экспериментальных результатов в течение одной экспериментальной кампании. Эффективным способом устранения различия между параметрами плазмы в разных импульсах является предионизация ВЧ-разрядной низкоплотной плазмой, которая создается малой рамочной антенной. Предионизация обеспечивает стабильность разрядов в течение всей экспериментальной кампании. Были измерены и оценены основные параметры предионизационной плазмы. Нестабільність розрядів Урагана-3М утрудняє відтворення експериментальних результатів на протязі однієї експериментальної кампанії. Ефективним способом усунення різниці між параметрами плазми в різних імпульсах є передіонізація ВЧ-розрядною низькощільною плазмою, яка створюється малою рамковою антеною. Передіонизація забезпечує стабільність розрядів на протязі всієї експериментальної кампанії. Були виміряні й оцінені основні параметри передіонізаційної плазми.